The effect of different variables on push-out tests in 3D-printed oval and round- shaped root canals: a methodological study - Gok, Tuba; Cankaya, Guzide; Sen, Bilge Hakan (Medical Journal Sweden Ab, 2025)
Objective: This study aimed to evaluate the effect of slice thickness (ST), plunger size (PS), shape and region of the root canal on push-out tests using standardized artificial root canals. Materials and methods: Two teeth with round and oval root canal anatomy were selected using cone beam computed tomography.Teeth were prepared, scanned with micro computed tomography and stereolithography data were obtained. Seventy-two round and 72 long oval artificial root canals were produced using a 3D printer. Root canals were obturated, then divided into two main groups (oval-round) and further divided into six subgroups (n = 12) according to ST (1, 1.5, and 2-mm) and PS (0.5, 0.75, and 1-mm). Push-out tests were performed and dislocation resistance values were calculated. The data were analyzed using the ANOVA two-way test (p = 0.05). Results: Different STs showed similar results in oval canals (p > 0.05). 1-mm ST showed higher results in round canals (p < 0.05). There was a significant difference between 0.75 and 1-mm PSs (p < 0.05). Middle and coronal regions showed similar results in oval canals (p > 0.05), and coronal region showed lower results in round canals (p < 0.05). Conclusion: ST, PS, root canal shape and region variables affected the dislocation resistance of core material in standardized root-filled canals.
Keywords: 3D printing; artificial root canal; dislocation resistance; push-out test; root canal treatment